The wishing tree - Faulkner, William 1897-1962.; Bolognese, Don. (New York Random House, 1964)
A strange boy with red hair leads a birthday-girl and her companions on a hunt for the wishing tree which brings them many surprising and magical adventures.
First publication of the author's only children's story. This version previously existed in a single typescript copy dated Feb. 5, 1927.
Keywords: Fantasy